Preoperative Underweight Patients with Upper Tract Urothelial Carcinoma Survive Less after Radical Nephroureterectomy - Kang, Ho Won (J Korean Med Sci, 2015)
The prognostic impact of body mass index (BMI) in patients with upper tract urothelial carcinoma (UTUC) is an ongoing debate. Our study aimed to investigate the prognostic role of BMI in patients treated with radical nephroureterectomy (RNU) for UTUC from a multi-institutional Korean collaboration. We retrospectively reviewed data from 440 patients who underwent RNU for UTUC at four institutions in Korea. To avoid biasing the survival estimates, patients who had previous or concomitant muscle-invasive bladder tumors were excluded. BMI was categorized into approximate quartiles with the lowest quartile assigned to the reference group. Kaplan-Meier and multivariate Cox regression analyses were performed to assess the influence of BMI on survival. The lower quartile BMI group showed significantly increased overall mortality (OM) and cancer specific mortality (CSM) compared to the 25%-50% quartiles and upper quartile BMI groups. Kaplan-Meier estimates showed similar results. Based on multivariate Cox regression analysis, preoperative BMI as a continuous variable was an independent predictor for OM and CSM. In conclusion, preoperative underweight patients with UTUC in Korea survive less after RNU. Preoperative BMI may provide additional prognostic information to establish risk factors. GRAPHICAL ABSTRACT: [Image: see text]